2014
DOI: 10.1088/0953-8984/26/21/215402
|View full text |Cite
|
Sign up to set email alerts
|

Pressure induced second-order structural transition in Sr3Ir2O7

Abstract: We conducted in situ angle dispersive high pressure x-ray diffraction experiments on Sr3Ir2O7 up to 23.1 GPa at 25 K with neon as the pressure transmitting medium. Pressure induces a highly anisotropic compressional behavior seen where the tetragonal plane is compressed much faster than the perpendicular direction. By analyzing different aspects of the diffraction data, a second-order structural transition is observed at approximately 14 GPa, which is accompanied by the insulating state to nearly metallic stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
30
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 32 publications
4
30
1
Order By: Relevance
“…Rietveld refinement suggests that the stacking sequence of the two perovskite bilayers is altered in the high-pressure phase, resulting in a novel modification of the Ruddlesden-Popper structure. In contrast to the study by Zhao et al [19], no evidence for a second-order structural transition around 14 GPa was found either at room temperature or at 20 K.…”
Section: Introductioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Rietveld refinement suggests that the stacking sequence of the two perovskite bilayers is altered in the high-pressure phase, resulting in a novel modification of the Ruddlesden-Popper structure. In contrast to the study by Zhao et al [19], no evidence for a second-order structural transition around 14 GPa was found either at room temperature or at 20 K.…”
Section: Introductioncontrasting
confidence: 99%
“…The lower compressibility along the c axis in the tetragonal phase appears to be alleviated by the phase transition to monoclinic symmetry. A Vinet equation of state was fitted to the pressure-volume data of the tetragonal phase, yielding a bulk modulus of B 0 = 157(4) GPa [B 0 = 4.3(3)], in agreement with the literature [19].…”
Section: B Results and Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Its structure has been regarded to be tetragonal (I4/mmm, with a = 3.9026 Å and c = 20.9300 Å [16,17]), but other studies also reveal that the crystal symmetry could be orthorhombic (Bbcb, with a = 5.522 Å, b = 5.521 Å, and c = 20.917 Å [18]) or even monoclinic (C2/c, with a = 5.5185 Å, b = 5.5099 Å, and c = 20.935 Å [19] [12]. In addition, whereas Zhao et al reported a second-order structure transition at ~15 GPa, Donnere et al only discovered a first-order structure transition at ~54 GPa [17].…”
mentioning
confidence: 99%